Implementasi pendidikan karakter peserta didik era generasi alpha di SMP Al-mushlih Telukjambe karawang - Salisah, Siti Khopipatu; Darmiyanti, Astuti; Arifudin, Yadi Fahmi (Peneliti.net, 2025)
This research examines the implementation of character education for alpha generation students at Al-Mushlih Telukjambe Karawang Middle School using a qualitative approach. Data was collected through in-depth interviews, participatory observation, and document analysis with research subjects consisting of school principals, teachers, and students. The research results show that the school has designed and implemented various character education programs that include activities inside and outside the classroom to instill values ​​such as honesty, discipline, responsibility and cooperation. Teachers play an important role in integrating character values ​​in the learning process and act as role models for students, while school principals support and monitor program implementation.